Análise de múltiplos cenários futuros climáticos e de uso e cobertura da terra na estimativa de vazões na bacia do rio salgado, semiárido nordestino - Silva, Alexandro Medeiros (2019)
Understanding the changes in flow behavior caused by climate change and changes in land use and cover in watersheds is vital, especially for watersheds located in a semi-arid environment. Given the above, this work aims to use together the hydrological modeling, modeling future scenarios of land use and cover and climate forecasts to identify possible future water vulnerabilities in the Rio Salgado River Basin - BHRS. To achieve this objective, the following methodological steps were performed: (a) analysis of changes in land use and land cover in the BHRS between 1985 - 2018; (b) prediction of future land use and land cover using the LCM model for the year 2050; (c) analysis of the multiple scenarios of atmospheric circulation models; (d) calibration and validation of the SWAT model for the period 1986–2017; (e) estimation of future flow to BHRS using the coupling between these models for the years 2030 to 2060. The results obtained during the calibration and validation stage of the SWAT model were considered good by the R², Nash indices, showing that the model has a good fit to the basin characteristics. Regarding the land use prediction model, the LCM validation was also considered satisfactory with a Kappa value of 0.77. The prediction for the year 2050 pointed to a significant increase in pasture and agriculture when compared to 2018, with 78% and 38%, respectively. Decreases were also identified in vegetation areas with -19% in forested areas and -33% in savannah areas. Two models of atmospheric circulation that presented the most distinct behaviors from historical data were selected, the IPSL-CM5ALR model and the NoerESM1-m model. Finally, future hydrological modeling of the basin was performed for eight scenarios linking land use and land cover predictions as well as climate model scenarios. For the NoerESM1-m model, in most scenarios, a decrease in the average monthly outflow that could reach 41% was identified, considerably impacting the water availability of the basin. In contrast, using the IPSL-CM5A-LR model, there was a forecast of increase in monthly average flow between 167% and 1045%